Analyzing the Impact of Financial Resources Management on Organizational Performance of Nigerian Manufacturing Sector - Ogbotor, Maxwell Smith; Ogbotor, Maxwell Smith (Journal of Accounting, Finance, and FinTech Advancements, 2025)
The Nigerian manufacturing sector, despite its critical role in driving economic growth and development, continues to face persistent challenges including poor infrastructure and financial mismanagement that have contributed to its subpar performance and low employment contribution. This study explores the impact of financial resources management on organizational performance in Nigeria’s manufacturing sector, guided by the Resource-Based View (RBV) theory. Employing a qualitative research approach, secondary data was collected from reputable sources, including academic journals, industry reports, and government publications. Thematic analysis revealed that effective financial resource management is crucial for organizational performance, with key areas driving financial success including working capital management, capital structure management, and good governance. Research highlights the importance of balancing short-term assets and liabilities, managing cash flow, and optimizing funding to boost performance. Good governance promotes transparency, accountability, and effective management, positively impacting firm performance. The study concludes that adopting robust financial management strategies can enhance organizational performance, resilience, and investment capacity, ultimately driving business success and sustainability. The findings provide insights for Nigerian manufacturing firms to strengthen their financials, improve competitiveness, and build a sustainable future.